Soil erosion risk and sediment transport within Paros Island (Greece). - Centeri, C.; Kristof, D.; Evelpidou, N.; Vassilopoulos, A.; Giotitsa, I. (5th International Congress of the European Society for Soil Conservation, Changing Soils in a Changing World: the Soils of Tomorrow, 2007)
Paros Island is part of the complex of Cyclades Islands, situated in the central Aegean Sea, Greece. It is characterized by the Mediterranean type of climate, with abrupt rainfalls and lower temperatures during winters and long term sunshine accompanied by dry periods during the summer, which constitutes a tough environment for the land. The low vegetation of the island leaves the ground exposed and very vulnerable to erosion. Also the recent change to the activities of the local people from agricultural to touristic ones and especially the abandonment of the agricultural terraces during the last 50 years has influenced the soil cover of the island in an unfavorable way, leading to total soil loss and exposure of the bedrock in many areas. Aggravating this fact, the slopes of the island are high in general terms thus making soil regeneration almost impossible. The soil that is transferred is either moving towards the small alluvial plains or, in most cases, is lost directly to the sea. In this paper there is an effort to depict the situation that currently exists on the island by pointing out the areas that still appear to be in a high risk for erosion and to estimate the average amount of soil loss. For the later the Universal Soil Loss Equation (USLE) was tested on the data of the island. The application of the USLE took place with the use of MapInfo and ArcGIS Tools.